Genome polarity of RNA viruses reflects the different evolutionary pressures shaping codon usage - Supinya Phakaratsakul (2019)
© 2018, Springer-Verlag GmbH Austria, part of Springer Nature. RNA viruses are classified by their genome polarity and replication strategies. Nucleotide composition and codon usage differ among virus groups, for instance positive-sense RNA (+ssRNA) viruses have higher GC-content than the other RNA virus groups. Codon usage of +ssRNA viruses is closer to humans showing significantly higher codon adaptation index (CAI) than those of negative-sense RNA (-ssRNA), double stranded RNA (dsRNA) and retroviruses. Ambisense viruses have high CAI comparable to that of +ssRNA virus despite their lower GC content, whereas dsRNA viruses have the lowest CAI. This may provide a benefit for +ssRNA viruses as their genomes are used as mRNA. However, analyses for influence of nucleotide composition on codon usage did not show a difference between +ssRNA and –ssRNA viruses. This suggests that genome composition and hence mutational pressure remain the major pressure causing the differences in codon usage among RNA viruses with different genome types.